2019
DOI: 10.1200/jco.2019.37.15_suppl.9007
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of TAK-788 in NSCLC with EGFR exon 20 insertions.

Abstract: 9007 Background: TAK-788 is an oral investigational EGFR/HER2 inhibitor under evaluation in NSCLC patients (pts) with EGFR exon 20 insertions. We report results of a phase 1/2 open-label, multicenter study (NCT02716116). Methods: Pts with advanced, previously treated NSCLC received daily TAK-788 in dose escalation and expansion cohorts based on tumor genotype. Antitumor activity was determined for pts with EGFR exon 20 insertions who received TAK-788 at the RP2D. Safety is reported for all pts across all dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…Early data for TAK‐788 in EGFR exon20ins NSCLC showed a confirmed overall response rate of 43%. Grade III adverse events have been observed in >50% of patients in trials of either inhibitor . The hope is that the benefit observed for patients with EGFR exon20ins NSCLC can translate to EGFR exon20ins UC, but this must be tested via UC‐focused clinical trials as lead by medical oncologists focusing on genitourinary cancers or via a basket trial with sufficient enrolment of UC to test this therapeutic hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Early data for TAK‐788 in EGFR exon20ins NSCLC showed a confirmed overall response rate of 43%. Grade III adverse events have been observed in >50% of patients in trials of either inhibitor . The hope is that the benefit observed for patients with EGFR exon20ins NSCLC can translate to EGFR exon20ins UC, but this must be tested via UC‐focused clinical trials as lead by medical oncologists focusing on genitourinary cancers or via a basket trial with sufficient enrolment of UC to test this therapeutic hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I/II trial, the objective response rate associated with TAK-788 also has decreased over time, from an initially reported 54% to a confirmed rate of 43%. 153 Early evidence of clinical activity has been seen with the EGFR-cMET bispecific antibody, JNJ-372, in an ongoing phase I trial. 129…”
Section: Exon 20 Insertionsmentioning
confidence: 99%
“…1,3,4,33,34 While the latter are sensitive to third-generation EGFR-TKIs, EGFR exon 20 insertions can be targeted with the specific inhibitor TAK-788. 35 Initial results from a phase I/II trial (NCT02716116) showed a disease control rate (DCR) of 89% with 54% of the patients achieving a partial response (confirmed + unconfirmed) and 35% stable disease. Overall, 23 of 24 evaluable patients (93%) showed a reduction in the tumor volume; side effects were consistent with other EGFR-TKIs.…”
Section: Egfr Mutations and Outcomes With Egfr-tkismentioning
confidence: 99%
“…Therefore, a phase III trial (n=318, 1:1 randomization) comparing TAK-788 with platinum/pemetrexed combination chemotherapy was initiated with enrolment starting in late 2019 (NCT04129502). 35…”
Section: Egfr Mutations and Outcomes With Egfr-tkismentioning
confidence: 99%